The Impact of Covid-19 on Activities of Banks - Assenova, Kamelia (Research Papers, 2025)
The Covid-19 pandemic is causing unpredictable disruption in the global economy. The pandemic affects every sector of the economy. As a result of this virus, the world economy is weakening, and this is also happening in Bulgaria.The banking sector is an important component of every economy. The banks have a fundamental role as providers of payment services, liquidity, and funding to businesses and individuals during the Covid-19 crisis.This paper aims to examine the impact of Covid-19 on bank liabilities and assets during the crisis and their role in the recovery of the economy. During the Covid-19 crisis, the business reduces its deposits because it does not have enough purchases and receivables. Firms need lending to cover inequality between in- and outflows, decide their liquidity problems, and ensure the working capital to restart business. The risk during the Covid-19 crisis rises and the quality of credit portfolio will deteriorate, by increasing non-performing loans.
Keywords: Banks; Credit; COVID-19